2020
DOI: 10.1097/mca.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Mediation analysis for the relationship between dyslipidemia and coronary artery disease via hypersensitive C-reactive protein in a case-control study

Abstract: Background The pathological basis of coronary artery disease (CAD) is atherosclerosis which is associated with inflammation and dyslipidemia. However, the involvement of hypersensitive C-reactive protein (hs-CRP) in lipid metabolism and how it affects the pathogenesis of CAD is uncertain. Objective To explore whether the relationship between dyslipidemia and CAD is partly mediated by hs-CRP levels. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The relationship between CRP and dyslipidemia could be explained by excessive lipids accumulating in the arterial wall, inducing an inflammatory response; it accelerates lipid deposition and amplifies the inflammation producing inflammatory factors such as CRP [ 34 ]. CRP can bind to LDL-C in atherosclerotic plaques, leading to complement activation, and promoting inflammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between CRP and dyslipidemia could be explained by excessive lipids accumulating in the arterial wall, inducing an inflammatory response; it accelerates lipid deposition and amplifies the inflammation producing inflammatory factors such as CRP [ 34 ]. CRP can bind to LDL-C in atherosclerotic plaques, leading to complement activation, and promoting inflammation and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…CRP can bind to LDL-C in atherosclerotic plaques, leading to complement activation, and promoting inflammation and atherosclerosis. Pan He et al reported that CRP plays a mediator role in the relationship between dyslipidemia and coronary arterial disease [ 34 ]. On the other hand, in normal conditions HDL-C promotes reverse cholesterol transport and inhibits LDL-C oxidation; however, under inflammatory conditions characterized by high levels of inflammatory markers such as IL-6, the antioxidant and anti-atherogenic capacity of HDL-C may be lower.…”
Section: Discussionmentioning
confidence: 99%
“…The mediation analysis revealed that hs-CRP played a partial mediating role in the relationship between dyslipidemia and CAD (8.27%). 6) To the best our knowledge, however, no study has directly combined HDL-C and hsCRP, two biological indicators, to explore the severity of CAD. In our work, we assumed that the CHR was a biomarker composed of inflammation marker and lipid cholesterol marker.…”
Section: Discussionmentioning
confidence: 99%
“…4,5) Recent studies suggested that that 8.27% of coronary artery disease with dyslipidemia is mediated by hsCRP levels. 6) However, no study has directly combined HDL-C and hsCRP, two biological indicators, to explore the severity of coronary artery disease. Therefore, this study suggested that hsCRP as a marker of the pro-inflammatory state and HDL-C as an anti-atherosclerosis component should be integrated into a single biomarker CHR in order to explore the correlation of CHR with the CAD severity and to predict the severity of coronary artery stenosis among CAD patients.…”
mentioning
confidence: 99%
“…Hs-CRP and HDL-C are both important in the process of atherosclerosis. Recent studies had suggested that the in uence of coronary heart disease by 8.27% with dyslipidemia was mediated by the hs -CRP levels 4 .…”
Section: Introductionmentioning
confidence: 99%